1991
DOI: 10.1113/jphysiol.1991.sp018698
|View full text |Cite
|
Sign up to set email alerts
|

The role of the beta 4‐subunit in determining the kinetic properties of rat neuronal nicotinic acetylcholine alpha 3‐receptors.

Abstract: SUMMARY1. Single-channel currents were recorded from Xenopus oocytes which had been injected with complementary RNAs (cRNAs) for the neuronal nicotinic acetylcholine receptor subunits ax3 and f4. The co-expression of ax3 aI. 1/84 gave rise to three different channel types with conductances of 22, 18 and 13 pS.2. The activity arising from the expression of these two subunits was compared with that observed when the a3 subunit was co-expressed with an alternative 18-subunit, 182. The az3fl4-receptors differed fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
68
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 33 publications
16
68
3
Order By: Relevance
“…All told, experiments on individual patches lasted 30 Ϫ 45 min, with no detectable rundown. This is in contrast to some reports of nAChR single-channel recordings (e.g., Papke and Heinemann, 1991;Hsiao et al, 2008) and may be due to the low ACh concentrations used and the low inherent activity of ␣3␤2 receptors.…”
Section: Electrophysiological Recordings and Analysiscontrasting
confidence: 52%
“…All told, experiments on individual patches lasted 30 Ϫ 45 min, with no detectable rundown. This is in contrast to some reports of nAChR single-channel recordings (e.g., Papke and Heinemann, 1991;Hsiao et al, 2008) and may be due to the low ACh concentrations used and the low inherent activity of ␣3␤2 receptors.…”
Section: Electrophysiological Recordings and Analysiscontrasting
confidence: 52%
“…It has been reported previously that ␣3␤4 nAChRs expressed in oocytes exhibit different single channel conductances (32), which may be attributed to distinct receptor stoichiometries. Previous studies of ␣3␤4␤3 nAChRs have suggested that the subunit stoichiometry of the receptor is confined to 2␣:3␤ proportion and the (␣3) 2 (␤4) 3 stoichiometry had been postulated for the ␣3␤4 receptor (33).…”
Section: Discussionmentioning
confidence: 99%
“…Such desensitization properties are directly related to the subunit composition. For instance, within the neuronal hetero-oligomeric subfamily, an ␣i␤2 oligomer desensitizes much faster than an ␣i␤4 oligomer (Papke and Heinemann, 1991;Bohler et al, 2001). Similarly ␣3␤j oligomers desensitize faster than ␣2␤j and ␣4␤j receptors.…”
Section: Physiologic Modes Of Action Of Acetylcholinementioning
confidence: 99%